2023
DOI: 10.3322/caac.21808
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer diagnosis and mortality beyond 15 years since quit in individuals with a 20+ pack‐year history: A systematic review

Karli K. Kondo,
Basmah Rahman,
Chelsea K. Ayers
et al.

Abstract: Current US lung cancer screening recommendations limit eligibility to adults with a pack‐year (PY) history of ≥20 years and the first 15 years since quit (YSQ). The authors conducted a systematic review to better understand lung cancer incidence, risk and mortality among otherwise eligible individuals in this population beyond 15 YSQ. The PubMed and Scopus databases were searched through February 14, 2023, and relevant articles were searched by hand. Included studies examined the relationship between adults wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Current work is being done to identify screening eligibility criteria in addition to 20+ pack-years smoking history and 15 years since quitting, that could better identify those at highest risk for the development of lung cancer. Particularly, Kondo et al suggest lung cancer risk not only persist past the 15 year since quitting criteria in current screening guidelines, but that it may remain increased for 2–3 decades ( 40 ). The Sybil model, a radiology-based learning model, has also been shown to predict future lung cancer risk, suggesting that artificial intelligence (AI) could be used in the future to identify people at the highest risk for the development of lung cancer, regardless of smoking history ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Current work is being done to identify screening eligibility criteria in addition to 20+ pack-years smoking history and 15 years since quitting, that could better identify those at highest risk for the development of lung cancer. Particularly, Kondo et al suggest lung cancer risk not only persist past the 15 year since quitting criteria in current screening guidelines, but that it may remain increased for 2–3 decades ( 40 ). The Sybil model, a radiology-based learning model, has also been shown to predict future lung cancer risk, suggesting that artificial intelligence (AI) could be used in the future to identify people at the highest risk for the development of lung cancer, regardless of smoking history ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The GDG requested that the ACS CrEST conduct a systematic review of lung cancer incidence, risk, and mortality beyond YSQ15 in persons with ≥20 pack-years of smoking for this guideline update. 43 The search identified articles through February 14, 2023, and yielded 22 studies from 26 publications. The reviewers concluded that, although the risk of lung cancer declined gradually after cessation compared with continuing smoking, there were no clinically significant differences when comparing individuals in the quit-year categories just before and beyond YSQ15 (six studies, moderate certainty of evidence [COE]).…”
Section: Years Since Quitting Smokingmentioning
confidence: 99%
“…The reviewers concluded that, although the risk of lung cancer declined gradually after cessation compared with continuing smoking, there were no clinically significant differences when comparing individuals in the quit-year categories just before and beyond YSQ15 (six studies, moderate certainty of evidence [COE]). 43 Similarly, compared with individuals WOLF ET AL.…”
Section: Years Since Quitting Smokingmentioning
confidence: 99%
See 2 more Smart Citations